2016
DOI: 10.1080/14740338.2016.1199681
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of QTc prolongation with atypical antipsychotic medications and selective serotonin reuptake inhibitors using a large ECG record database

Abstract: This study suggests that atypical antipsychotic drugs and SSRIs are less likely to be associated with QTc prolongation in clinical settings. In addition, age showed a significant association with the QTc interval. Further studies with well-characterized cohorts are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…After examining the association of the QTc interval with certain drugs, Yun et al [ 11 ] suggested that famotidine administration can prolong the QTc interval and increase the proarrhythmic potential. Additionally, Park et al [ 13 ] concluded that selective serotonin reuptake inhibitors are less likely to be associated with QTc interval prolongation. The ECG-ViEW II contains previous ECG-ViEW data and an additional 270 thousand ECGs, allowing researchers to study the relationship between the QT interval and drug administration.…”
Section: Resultsmentioning
confidence: 99%
“…After examining the association of the QTc interval with certain drugs, Yun et al [ 11 ] suggested that famotidine administration can prolong the QTc interval and increase the proarrhythmic potential. Additionally, Park et al [ 13 ] concluded that selective serotonin reuptake inhibitors are less likely to be associated with QTc interval prolongation. The ECG-ViEW II contains previous ECG-ViEW data and an additional 270 thousand ECGs, allowing researchers to study the relationship between the QT interval and drug administration.…”
Section: Resultsmentioning
confidence: 99%
“…Although meta-analyses have indicated that different antipsychotics have different effects on QTc prolongation, 5 several studies based on real-world data showed no association between atypical antipsychotics use and QTc prolongation. 20,21,30,31 The association between antipsychotics and QTC prolongation needs to be further explored with a large longitudinal follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…In patients admitted for sertraline overdose (>200 mg), incidence of QTc interval >500 ms was 6% (6/103); incidence of QTc interval greater than 440 ms was 40% (41/103) . Incidence of maximum QTcB interval prolongation (males, QTcB >450 ms; females, QTcB >460 ms) was 7.9% (3/38) in an analysis of recordings from the Electrocardiogram Vigilance With Electronic Data Warehouse database in which dosing and concomitant medications were unknown . A case study describing a patient admitted to intensive care after a multiple‐drug overdose including 2250 mg of sertraline, 200 mg of diazepam, and 400 mg of temazepam reported an increase in QTc from 370 milliseconds at admission to 525 milliseconds 1 day later .…”
Section: Discussionmentioning
confidence: 99%
“…Although not a direct relationship, reduction of delayed rectifier potassium/hERG current is considered a surrogate marker of delayed cardiac repolarization . No significant effect of sertraline on QTc was observed in a population‐based cohort study comparing SSRI‐treated adults with untreated individuals or in either of 2 retrospective analyses of electrocardiogram (ECG) records . Nonetheless, pharmacovigilance assessments indicate that QTc prolongation may occur after ingestion of suprathreshold sertraline doses …”
mentioning
confidence: 99%
See 1 more Smart Citation